Novel invisible markers for monitoring cracks on masonry structures. (20th September 2021) - Bal, İhsan E.; Dais, Dimitris; Smyrou, Eleni; Sarhosis, Vasilis
Highlights: Novel near-infrared (NIR) markers were developed for crack monitoring. Painted markers perform better than the tape markers both in terms of accuracy and precision. Precision and accuracy of 0.05 mm has been achieved. Markers are almost invisible and thus aesthetically pleasing for historical structures. The method can be used by non-technical people; citizen involvement is encouraged. Abstract: This paper presents a proof of concept for monitoring masonry structures using two different types of markers which are not easily noticeable by human eye but exhibit high reflection when subjected to NIR (near-infrared) wavelength of light. The first type is a retroreflective marker covered by a special tape that is opaque in visible light but translucent in NIR, while the second marker is a paint produced from infrared reflective pigments. The reflection of these markers is captured by a special camera-flash combination and processed using image processing algorithms. A series of experiments were conducted to verify their potential to monitor crack development. It is shown that the difference between the actual crack width and the measured was satisfactorily small. Besides that, the painted markers perform better than the tape markers both in terms of accuracy and precision, while their accuracy could be in the range of 0.05 mm which verifies its potential to be used for measuring cracks in masonry walls or plastered and painted masonry surfaces. The proposed method can be particularly useful for heritage structures, and especially for acute problems like foundation settlement. Another advantage of the method is that it has been designed to be used by non-technical people, so that citizen involvement is also possible in collecting data from the field.